NATURE IN THE WORKS OF YASUNARI KAWABATA (Heritage, 2020)
There is a strong connection between Japanese culture and nature, to the extent that they can be considered synonyms. Magnificent and cruel nature relentlessly imposed on the inhabitants to reduce their weaknesses and helplessness by cultural work, to make the islands the places where life turns into art and where the creation of a cultural tradition is enabled, in which different and fascinating art forms are expressed. In this paper, the cult of nature is analyzed, which occupies a special place in the works of Yasunari Kawabata. The focus is on the novels Snow Country and  Thousand Cranes, in which the perception of nature is given through the prism of Kawabata's view on the fragile beauty of human life before the fear of the whirlpool of transience. Man's attitude towards nature in the works of Kawabata is also reflected in the mysterious role that phenomena in nature have in the formation of characters. The merging  of man with nature and the harmony of man and nature are the main aspects of the interpretation of nature in the works of Kawabata, and the multidimensionality of his narration emerges from them.
Keywords: Yasunari Kawabata, cult of nature, harmony of man and nature, Snow Country, Thousand Cranes